Regulation of IL-1β–induced NF-κB by hydroxylases links key hypoxic and inflammatory signaling pathways - Scholz, Carsten C.; Cavadas, Miguel A. S.; Tambuwala, Murtaza M.; Hams, Emily; Rodríguez, Javier; von Kriegsheim, Alex; Cotter, Philip; Bruning, Ulrike; Fallon, Padraic G.; Cheong, Alex; Cummins, Eoin P.; Taylor, Cormac T. (Proceedings of the National Academy of Sciences - PNAS, 2013)
Hypoxia is a prominent feature of chronically inflamed tissues. Oxygen-sensing hydroxylases control transcriptional adaptation to hypoxia through the regulation of hypoxia-inducible factor (HIF) and nuclear factor κB (NF-κB), both of which can regulate the inflammatory response. Furthermore, pharmacologic hydroxylase inhibitors reduce inflammation in multiple animal models. However, the underlying mechanism(s) linking hydroxylase activity to inflammatory signaling remains unclear. IL-1β, a major proinflammatory cytokine that regulates NF-κB, is associated with multiple inflammatory pathologies. We demonstrate that a combination of prolyl hydroxylase 1 and factor inhibiting HIF hydroxylase isoforms regulates IL-1β–induced NF-κB at the level of (or downstream of) the tumor necrosis factor receptor-associated factor 6 complex. Multiple proteins of the distal IL-1β–signaling pathway are subject to hydroxylation and form complexes with either prolyl hydroxylase 1 or factor inhibiting HIF. Thus, we hypothesize that hydroxylases regulate IL-1β signaling and subsequent inflammatory gene expression. Furthermore, hydroxylase inhibition represents a unique approach to the inhibition of IL-1β–dependent inflammatory signaling.